The best lower body body-weight exercises - Edwards, A. (University of Cambridge, 2020)
If you are stuck at home self-isolating or social distancing without access to a gym then this series is perfect for you. In this blog post we`ll review some of the best bodyweight lower body exercises which require little or no equipment and serve as great alternatives to gym based free weight and machine exercises.